Survival of patients with prostate cancer - Fabienne Camilo da Silveira Pirajá; Rafael Bandeira Lages; Uylma Assunção Costa; João Batista Mendes Teles; Viriato Campelo (Universidade de Fortaleza, 2013)
Objective: To analyze the survival after five years among patients treated of prostate cancer at Hospital São Marcos. Methods: A descriptive population-based epidemiological study performed in Teresina-PI, evaluating a hospital cohort consisting of 71 patients of Hospital São Marcos, enrolled in Hospital Cancer Registry (HCR) from 2000 to 2001, under ICD10 -C61. The variables considered in the evaluation of survival were: age group, tumor staging and skin color. The Kaplan-Meier method was used in the calculation of survival functions in five years and the Kruskal-Wallis test in comparison between variables. Results: The specific survival rate for prostate cancer was of 78.5% in five years. The death risk in this study increased with age and advanced stage at diagnosis (aged 80 or above = 60%; and stage IV = 63%). The Kruskal-Wallis test showed no statistically significant variation between groups. Conclusion: The age and advanced stage at diagnosis decreased patients' survival.